2020
DOI: 10.1093/cercor/bhaa318
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Border between the Visual and Posterior Parietal Cortex of Mice

Abstract: The posterior parietal cortex (PPC) contributes to multisensory and sensory-motor integration, as well as spatial navigation. Based on primate studies, the PPC is composed of several subdivisions with differing connection patterns, including areas that exhibit retinotopy. In mice the composition of the PPC is still under debate. We propose a revised anatomical delineation in which we classify the higher order visual areas rostrolateral area (RL), anteromedial area (AM), and Medio-Medial-Anterior cortex (MMA) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 81 publications
(96 reference statements)
0
15
0
Order By: Relevance
“…We recorded in medial PPC (mPPC/V2m), where there is less innervation from primary visual cortex or thalamic visual areas (Reep et al, 1994;Nitz, 2009;Wilber et al, 2015;Olsen and Witter, 2016;Olsen et al, 2017). However, it is important to note that analogous anatomical regions in mice are considered part of the higher visual cortex (Glickfeld and Olsen, 2017;Hovde et al, 2019;Gilissen et al, 2021) and that mPPC receives dense afferents from dysgranular RSC (dRSC) where visually evoked responsivity has been reported (Fischer et al, 2020;Mao et al, 2020;Powell et al, 2020;Zhuang et al, 2017). Unsurprisingly, we find that a subset of PPC neurons were sensitive to the egocentric position of the visual target.…”
Section: Mechanisms Of Ppc Adaptation and Efferent Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recorded in medial PPC (mPPC/V2m), where there is less innervation from primary visual cortex or thalamic visual areas (Reep et al, 1994;Nitz, 2009;Wilber et al, 2015;Olsen and Witter, 2016;Olsen et al, 2017). However, it is important to note that analogous anatomical regions in mice are considered part of the higher visual cortex (Glickfeld and Olsen, 2017;Hovde et al, 2019;Gilissen et al, 2021) and that mPPC receives dense afferents from dysgranular RSC (dRSC) where visually evoked responsivity has been reported (Fischer et al, 2020;Mao et al, 2020;Powell et al, 2020;Zhuang et al, 2017). Unsurprisingly, we find that a subset of PPC neurons were sensitive to the egocentric position of the visual target.…”
Section: Mechanisms Of Ppc Adaptation and Efferent Targetsmentioning
confidence: 99%
“…In rodents, pursuit requires the dorsal striatum, superior colliculus (SC), and zona incerta (Schiller and Stryker, 1972;Cooper et al, 1998;Hoy et al, 2016Hoy et al, , 2019Shang et al, 2019;Zhao et al, 2019;Kim et al, 2019). Sensory cues relevant to predatory behavior (e.g., the sight, sound, or smell of prey) are potentially combined in areas such as posterior parietal cortex (PPC), which possesses reciprocal connectivity to sensorimotor cortical regions and projects to the SC and dorsal striatum (Reep et al, 1994;Wilber et al, 2015;Hovde et al, 2019;Gilissen et al, 2021). Lateralized PPC damage produces hemispatial neglect, impairing detection and orientation to stimuli present in contralateral space (Bisiach and Luzzatti, 1978;Behrmann et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that PPC is involved in resolving sensory conflict during auditory-visual discrimination tasks (Song et al, 2017 ) and is involved in transferring sensory-specific signals to higher order association areas (Gallero-Salas et al, 2021 ). RL and AM, two HVAs, are considered part of the PPC because they display connectivity patterns similar to other components of the PPC (Gilissen et al, 2021 ).…”
Section: Cross-modal Recruitmentmentioning
confidence: 99%
“…Our neuronal recordings were conducted in medial PPC (mPPC/V2m) where there is less direct innervation from primary visual cortex or thalamic visual areas (Reep et al, 1994;Nitz, 2009;Wilber et al, 2015;Olsen and Witter, 2016;Olsen et al, 2017). However, it is important to note that analogous anatomical regions in mice are considered part of the higher visual cortex (Glickfeld and Olsen, 2017;Hovde et al, 2019;Gilissen et al, 2020) and that mPPC receives dense afferents from dysgranular RSC (dRSC) where visually-evoked responsivity has been reported (Fischer et al, 2020;Mao et al, 2020;Powell et al, 2020;Zhuang et al, 2017). Taken together, it seemed highly probable that PPC activity would be influenced by visual information and consistent with this hypothesis, we report that a subset of PPC neurons were sensitive to the egocentric position of the visual target (Figure 6).…”
Section: Mechanisms Of Ppc Adaptation and Efferent Targetsmentioning
confidence: 99%
“…Multisensory cues that define the context of predatory behavior (e.g. the sight, sound, or smell of prey) are potentially combined in association cortices such as posterior parietal cortex (PPC) which possesses reciprocal connectivity to sensorimotor cortical regions and projects to the SC and dorsal striatum (Reep et al, 1994;Wilber et al, 2015;Hovde et al, 2019;Gilissen et al, 2020). PPC damage produces hemispatial neglect, which manifests as an inability to detect or orient to stimuli present in space contralateral to the site of lesion (Bisiach and Luzzatti, 1978;Behrmann et al, 1997).…”
Section: Introductionmentioning
confidence: 99%